Pendidikan Agama Islam Dan Implikasinya Terhadap Karakter Siswa Di Yayasan Islam Amalia Medan - Rizky Agustia (Getpress Management Journals, 2025)
This study examines the implications of teaching Islamic Religious Education (PAI) on student character building at Amalia Islamic Foundation Medan using a qualitative approach with field studies and interviews with teachers and students as primary data, and literature review as secondary data. The results showed that PAI teachers not only delivered material, but also provided personal advice and guidance that was effective in instilling Islamic values. Teachers act as models and motivators in shaping students' Islamic behavior, which is reflected in daily life. Students experience applicable character learning, not just theory, so that they are able to apply religious values in various situations. Motivation and spiritual reinforcement given consistently also help increase students' faith and piety. This study confirms that PAI teaching has a strategic role in building the character of Islamic people through a personalized and contextual approach.